IJARAH AND THE SHARING ECONOMY: A FIQH AL-MUAMALAT PERSPECTIVE ON THE PHENOMENON OF DIGITAL RENTALS IN THE PLATFORM ERA - Dida Novandika; Muhamad Zen (J-MD Jurnal Manajemen Dakwah, 2025)
This study examines the application of the ijarah contract within the digital sharing economy, focusing on platforms such as Gojek, Grab, and Airbnb. Employing a systematic literature review and qualitative content analysis, the research investigates academic literature, DSN-MUI fatwas, Financial Services Authority (OJK) regulations, and normative principles of the Qur’an. The findings indicate that the ijarah contract remains relevant in digital economic practices but faces critical challenges, including uncertainty (gharar), information transparency, and consumer protection. The variant Ijarah Muntahiyah bi al-Tamlik (IMBT) is considered more adaptive for long-term digital transactions, as it provides ownership certainty at the end of the contract. DSN-MUI Fatwas No. 112/2017 and No. 117/2018 offer normative legitimacy, while OJK regulations strengthen legal certainty, transparency, and consumer protection. Contemporary research (Muhamad Zen, 2021; 2022) further highlights the importance of clear objects, pricing, duration, and dispute resolution mechanisms. These results are consistent with the Qur’anic principle in Q.S. Al-Qaṣaṣ [28]:26, emphasizing al-quwwah (competence) and al-amānah (trustworthiness) as ethical foundations. This study contributes to the development of contemporary fiqh muamalah by integrating classical theory, fatwas, regulations, and digital practices. Practical implications include strengthening contract transparency in digital platforms, designing Sharia-compliant tax regulations, and improving consumer protection mechanisms.